Physical activity intervention effects on perceived stress in working mothers: the role of self-efficacy - Mailey, Emily L.; McAuley, Edward (My University, 2014)
Working mothers often report elevated stress, and efforts to improve their coping resources are needed to buffer the detrimental effects of stress on health. This study examined the impact of changes in physical activity, self-efficacy, and self-regulation across the course of a brief intervention on subsequent levels of stress in working mothers. Participants (N=141) were randomly assigned to an intervention or control condition (2:1 ratio). The intervention was conducted in Illinois between March 2011-January 2012 and consisted of two group-mediated workshop sessions with content based on Social Cognitive Theory. Participants completed measures of physical activity, self-efficacy, self-regulation, and perceived stress at baseline, immediately post-intervention, and 6-month follow-up. Stress levels declined across the 6-month period in both groups. Changes in stress were negatively associated with changes in self-efficacy and self-regulation among intervention participants only. Regression analyses revealed the intervention elicited short-term increases in physical activity, self-efficacy, and self-regulation, but only changes in self-efficacy predicted perceived stress at 6-month follow-up. These results suggest that enhancing self-efficacy is likely to improve working mothers’ perceived capabilities to cope with stressors in their lives. Future interventions should continue to focus on increasing self-efficacy to promote improvements in physical activity and psychological well-being in this population.
Keywords: Working mothers; Physical activity; Self-efficacy; Stress